Olutasidenib in combination with azacitidine induces durable complete remissions in patients with relapsed or refractory mIDH1 acute myeloid leukemia: a multicohort open-label phase 1/2 trial - Jorge E. Cortes; Gail J. Roboz; Maria R. Baer; Brian A. Jonas; Gary J. Schiller; Karen Yee; P. Brent Ferrell; Jay Yang; Eunice S. Wang; William G. Blum; Alice Mims; Hua Tian; et al. (Journal of Hematology & Oncology)
Abstract Background Olutasidenib is a potent, selective, oral, small molecule inhibitor of mutant IDH1 (mIDH1) which induced durable remissions in high-risk, relapsed/refractory (R/R) mIDH1 AML patients in a phase 1/2 trial. We present a pooled analysis from multiple cohorts of the phase 1/2 trial of patients with R/R AML who received combination olutasidenib and azacitidine therapy. Methods Adult patients with mIDH1 R132 AML received 150 mg olutasidenib twice daily plus standard-of-care azacitidine (OLU + AZA) and were evaluated for response and safety. Results Sixty-seven patients with R/R mIDH1 R132 AML received combination OLU + AZA. Median age was 66 years (range 28–82) and 54% were male. Most patients (83%) had 2 + prior regimens, including a hypomethylating agent in 40%, IDH1 inhibitor therapy in 31% (olutasidenib in 24%), and hematopoietic stem cell transplant in 10%. Cytogenetic risk was intermediate in 72%, poor in 18% and unknown in 10%. CR/CRh was achieved in 21/67 (31%; 95% CI 21–44) patients, with a median duration of 14.7 months (95% CI 4.6-not reached). CR was achieved in 18/67 (27%; 95% CI 17–39) patients, with median duration of 20.3 months (95% CI 3.7-not reached). Overall response (partial remission or better) was achieved in 34/67 (51%; 95% CI 38–63) patients. Median overall survival was 12.9 months (95% CI 18.7–19.3). In a subset analysis excluding patients who had prior OLU exposure (N = 51), CR/CRh was achieved in 19/51 (37%; 95% CI 24–52) patients, CR was achieved in 16/51 (31%; 95% CI 19–46), and overall response was achieved in 30/51 (59%; 95% CI 44–72). In patients who achieved CR/CRh and were transfusion-dependent at baseline, transfusion independence (RBC and platelets) was achieved in 64% (7/11) and 57% (4/7) of patients, respectively. The most common Grade 3 or 4 adverse events (> 20% patients) were decreased platelet count (37%), red blood cell count (25%), and neutrophil count (24%). Six patients (9%) experienced differentiation syndrome. Four (6%) discontinued treatment due to an adverse event. Conclusions Olutasidenib plus azacitidine induced high response rates and durable remissions with a tolerable side effect profile in patients with R/R AML with diverse treatment histories. The results represent another therapeutic option for patients with mIDH1 AML who may benefit from a targeted therapy. Trial registration NCT02719574.